2011
DOI: 10.1002/acr.20553
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between early bone mineral density changes and long‐term function and radiographic progression in rheumatoid arthritis

Abstract: Objective. To ascertain whether bone mineral density loss during the first year of treatment for early rheumatoid arthritis (RA) as assessed by dual x-ray absorptiometry (DXA) is associated with long-term function, quality of life, and radiographic progression. Methods. Early RA patients, prior to commencing disease-modifying antirheumatic drug therapy, underwent evaluation with DXA scans of both hands, femoral neck, and lumbar spine at the time of diagnosis, then at 1 year and final followup at >6 years. Clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 13 publications
0
13
0
2
Order By: Relevance
“…Several previous studies have identified BMD loss as a predictor of long‐term joint damage over periods of up to 20 years (). More recently, Bejarano and coworkers () also demonstrated an association between DXA‐measured hand BMD loss in the first year and long‐term radiographic progression (6.4‐year followup) in a smaller (n = 64) early RA cohort. However, they concluded that hand BMD loss did not provide any additional information over and above the presence of erosions on baseline radiographs of the hands and feet.…”
Section: Discussionmentioning
confidence: 89%
“…Several previous studies have identified BMD loss as a predictor of long‐term joint damage over periods of up to 20 years (). More recently, Bejarano and coworkers () also demonstrated an association between DXA‐measured hand BMD loss in the first year and long‐term radiographic progression (6.4‐year followup) in a smaller (n = 64) early RA cohort. However, they concluded that hand BMD loss did not provide any additional information over and above the presence of erosions on baseline radiographs of the hands and feet.…”
Section: Discussionmentioning
confidence: 89%
“…A longitudinal study of 50 patients with early RA (whose hand BMD was measured at baseline, 6 and 12 mo) indicated that the baseline value of hand BMD was associated with radiographic scores at 12 mo [27] . Another longitudinal study consisting of 64 patients with RA confirmed the predictive value of hand BMD loss in the first year for the subsequent radiographic progression (6.4 year follow up) [35] . A longitudinal study by Black et al [37] showed hand BMD loss in the first 6 mo might be a predictor for erosions at 12 mo.…”
Section: Hand Bone Mass and Functional Outcomementioning
confidence: 93%
“…Several longitudinal studies suggested that early hand bone loss may have predictive value to determine which patients with early RA will develop further radiographic progression or have poor functional status [26,27,31,35,37] . However, there are contrasting results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Erken dönem RA'da görülen sinovit ve periartiküler kemik kaybı kemik hasarının oluşumu ve progresyonu için belirleyicidir (8). Yapılan çalışmalarda, erken dönem RA'da, elde görülen kemik kaybı ile radyolojik ilerleme ilişkili bulunmuştur (11,12). Erken dönem RA'lı hastalarda saptanan el KMY kaybı, bir yıldan daha fazla zamandır remisyonda olan hastalarda %0,03 iken, düşük hastalık aktivitesi olanlarda %2,03, yüksek hastalık aktivitesi olanlarda ise %3,13 olarak saptanmıştır (13).…”
unclassified